Myocardial infarction in mice – tips and pitfalls on the surgical and echocardiographic techniques - Śliwka, Joanna; Kumaszka, Bartłomiej; Garbacz, Marcin; Pakuło, Sławomir; Nowak, Karolina; Domagała, Maciej; Jaźwiec, Tomasz; Zandecki, Mateusz; Cichoń, Tomasz; Nożyński, Jerzy; Smolarczyk, Ryszard; Szala, Stanisław; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Cardiovascular research on myocardial physiology is often based on animal models of heart ischaemia. The model of left anterior descending (LAD) ligation in the mouse has been widely used to test various experimental hypotheses. However, there are significant discrepancies among studies not only in terms of technical aspects of the model, but more importantly, in early and late outcomes. Moreover, there is no step-by-step guide on how to create the model, avoid difficulties, pitfalls and technical hazards, and thus minimize early and late mortality. This paper is intended to serve as a reference for cardiovascular laboratories wishing to successfully start and maintain a reliable and reproducible model of LAD ligation in mice.